Charliebird [videorecording (DVD)] - Smart, Samantha; Smart, Samantha; Perez, Gabriela Ochoa; Fazio, Gabe, 1973- (Freestyle Digital Media, 2026)
A music therapist meets a defiant teenage patient in this elegant, timely drama set in rural Texas.